A22 A HIDDEN CAUSE OF DRUG-INDUCED LIVER FAILURE. (1st March 2018) - Bergeron, F; Hussaini, T; Yoshida, E M; Marquez, V
Abstract: Background: Nimesulide is a non-steroidal anti-inflammatory drug with relative selectivity for cyclooxygenase-2 enzyme marketed in 1985. Nimesulide was never approved for use in Canada, United States, United Kingdom, Australia, or New Zealand due to safety concerns. Multiple reports in the literature have linked nimesulide to severe liver injuries ranging from marked aminotransferase elevation to acute liver failure (ALF), need for liver transplantation, and death. Such reports have led to nimesulide's withdrawal from the market in Finland and Spain in 2002, and in Ireland in 2007; however, it remains widely available in more than 50 countries worldwide. The mechanism for its hepatotoxicity remains unknown. Aims: We report a fatal case of ALF sustained by consumption of a "herbal" product purchased in Canada. Methods: Chart review. Results: A 52-year-old female developed jaundice and malaise with rapid progression to ALF. Her past medical history was significant for type 2 diabetes, hypothyroidism, sickle cell trait, and breast adenocarcinoma in remission. Her medications included metformin, levothyroxine, tamoxifen, and "herbal" medications (Arjun heart tonic, R. Pyine and Hari tablets). She had no risks factors for chronic liver disease and family history was non-contributory. After initial presentation to a community hospital, she was transferred to a liver transplant center where she developed encephalopathy associated with worsening liver function. Serologies were negative for viral, auto-immune, and metabolic etiologies. Acetaminophen and ethanol levels were undetectable. Imaging showed patent hepatic vasculature, normal biliary ducts and hepatic parenchyma. Her clinical status deteriorated further and she underwent an orthotropic liver transplant three weeks after presentation. The liver explant appeared pale and shrunken. Histopathologic examination showed subacute massive paracinar and periportal necrosis compatible with drug-induced liver injury. Since the patient's labeled "herbal" medications did not include hepatotoxic drugs, the "herbal" products were analyzed by our medicinal chemistry lab and revealed presence of high concentrations of nimesulide and chlordiazepoxide within two of the three herbal products. Four days postoperatively, she passed away due to sepsis and multiorgan failure. Conclusions: In Canada, 73% of the population regularly consumes herbal products. The majority (59%) of herbal medicines sold in North America contain ingredients that are not listed on the label. Here, we report a fatal case of ALF sustained by consumption of a commercially available herbal product that contained a known pharmaceutical product that is neither approved nor marketed in Canada. This case highlights the urgent need for governmental regulation and consumer safety policies regarding the manufacture, importation and dispensing of herbal/natural products to prevent serious adverse events. Funding Agencies: None